2018
DOI: 10.1371/journal.pbio.2004194
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic characterization and comparison of T helper 17 and induced regulatory T cells

Abstract: The transcriptional network and protein regulators that govern T helper 17 (Th17) cell differentiation have been studied extensively using advanced genomic approaches. For a better understanding of these biological processes, we have moved a step forward, from gene- to protein-level characterization of Th17 cells. Mass spectrometry–based label-free quantitative (LFQ) proteomics analysis were made of in vitro differentiated murine Th17 and induced regulatory T (iTreg) cells. More than 4,000 proteins, covering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 79 publications
(83 reference statements)
1
23
0
Order By: Relevance
“…The expression of SATB1 in distinct Th and Treg cells is shown to be conserved between human and mouse (Ribeiro de Almeida et al., 2009, Ahlfors et al., 2010, Beyer et al., 2011). SATB1 expression has been previously reported to be upregulated in mouse Th17 cells (Ciofani et al., 2012, Mohammad et al., 2018). However, we found SATB1 transcription to be downregulated during human Th17 cell differentiation (Tuomela et al., 2012, Tuomela et al., 2016).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The expression of SATB1 in distinct Th and Treg cells is shown to be conserved between human and mouse (Ribeiro de Almeida et al., 2009, Ahlfors et al., 2010, Beyer et al., 2011). SATB1 expression has been previously reported to be upregulated in mouse Th17 cells (Ciofani et al., 2012, Mohammad et al., 2018). However, we found SATB1 transcription to be downregulated during human Th17 cell differentiation (Tuomela et al., 2012, Tuomela et al., 2016).…”
Section: Resultsmentioning
confidence: 97%
“…Our recent study identified conserved and diversified gene signatures from the comparison of human and mouse transcriptomes during Th17 cell polarization (Tuomela et al., 2016). To further establish the level of dissimilarity, we made direct comparison with data from a recently published proteomics dataset from mouse Th17 cells cultured for 72 hr (Mohammad et al., 2018). The proteome profiles of CD4+ T cells 72 hr after TCR activation and Th17 polarization were compared using the aforementioned mouse data and the human data from the current study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, very few studies have been performed in mouse Th cells. A recent study investigated the differentiation of T cells to Th17 and iTreg subsets providing a valuable resource for further characterization of these cell types. In this study, we set out to perform comprehensive proteome profiling of mouse Th1 and Th2 cells.…”
mentioning
confidence: 99%